Ferroptosis: a new mechanism of traditional Chinese medicine for treating ulcerative colitis - Wang, Yingyi; Hao, Yanwei; Yuan, Lingling; Tian, Huaie; Sun, Xuhui; Zhang, Yi (Frontiers in Pharmacology, 2024)
Ulcerative colitis (UC), a subtype of inflammatory bowel disease, manifests with symptoms such as abdominal pain, diarrhea, and mucopurulent, bloody stools. The pathogenesis of UC is not fully understood. At present, the incidence of UC has increased significantly around the world. Conventional therapeutic arsenals are relatively limited, with often poor efficacy and many adverse effects. In contrast, traditional Chinese medicine(TCM) holds promise due to their notable effectiveness, reduced recurrence rates, and minimal side effects. In recent years, significant progress has been made in the basic research on TCM for UC treatment. It has been found that the inhibition of ferroptosis through the intervention of TCM can significantly promote intestinal mucosal healing and reverse UC. The mechanism of action involves multiple targets and pathways.Aim of the review:This review summarizes the experimental studies on the targeted regulation of ferroptosis by TCM and its impact on UC in recent years, aiming to provide theoretical basis for the prevention, treatment, and further drug development for UC.Results: Ferroptosis disrupts antioxidant mechanisms in intestinal epithelial cells, damages the intestinal mucosa, and participates in the pathological process of UC. TCM acts on various pathways such as Nrf2/HO-1 and GSH/GPX4, blocking the pathological progression of ferroptosis in intestinal epithelial cells, inhibiting pathological damage to the intestinal mucosa, and thereby alleviating UC.The diverse array of TCM single herbs, extracts and herbal formulas facilitates selective and innovative research and development of new TCM methods for targeting UC treatment. Although progress has been made in studying TCM compound formulas, single herbs, and extracts, there are still many issues in clinical and basic experimental designs, necessitating further in-depth scientific exploration and research.